Ecocentrism as Theoretical Framework for Environmental Ethics - Francis Tete (Universitas Negeri Makassar, 2022)
Environmental ethics has emerged as the philosophical response to the threat of a looming environmental apocalypse. Aside from ethical issues arising from our relation to fellow humans, our survival and wellbeing and the wellbeing of generations after us depend on how we live with, what we do to, and how our lives affect other co-inhabitants of the earth like tigers, fishes, rivers and mangroves. Recent philosophical response to the ethics of environmental concern has led to the emergence of two model theoretical frameworks, anthropocentrism and ecocentrism. Indeed, all environmental philosophy can be divided into anthropocentrism and ecocentrism (Callicott, 1999), otherwise labelled secondary and primary environmental ethics (Rolston, 1988). Whereas the former seeks care for the environment from the perspective of its instrumental value to mankind, the latter approaches human relation to nature on the merits of natureâ€™s inherent value. On our choice of which of these theories to build our environmental ethic depends how far we go in responding to the critical challenges posed by the depleting of natural resources, the loss of biodiversity, the menace of climate change and the spectre of global environmental degradation. This article exposes the ecocentric framework with the objective of outlining its essential elements, thereby making it accessible for philosophical appraisal. Beyond profiling the distinctive traits of ecocentrism, this article argues that its theoretical framework opens a new vista for moral philosophy, provides the radically new dimension in moral theory without which every prospect of an effective environmental ethics falters in want of an appropriate philosophical foundation.Â